Peran Warna Pada Desain Interior Kedai Jamu Mahidana Bandung Bagi Pengalaman Pengunjung - Setiawan, Clement Charisma; Darmayanti, Tessa Eka (Waca Cipta Ruang, 2024)
Color is one of the most important aspects on interior elements so that interior design in general could serve the function that is expected. Color can affect people’s feeling and behavior when they are doing activities indoor, in this case is cafe. Color scheme that is irrelevant with the cafe’s concept can affect user’s experience negatively in various factors such as feeling, behavior, and comfort. Therefore, there are many cafes in Bandung that carefully plan their color scheme, one of which is Mahidana herbs cafe. This cafe has its own uniqueness amidst lots of coffeeshops in Bandung. Mahidana, which only serves Traditional Indonesian Herbal Drinks has a different color scheme compared to most cafes in general. The purpose of this research is to know the role of interior color to the user’s experience while enjoying the drinks in this cafe. In this research, the qualitative method is applied. This includes the observation of the cafe and interviewing cafe’s consumers. From this research, the importance of color is known because the chosen color palette can affect the feeling and experience of the user who visits Mahidana herbs cafe.